Eating disorders in the world of sport: the experiences of rhythmic gymnasts - Komanthi, K.; Theodosis, E.; Apostolos, S. (Journal of Biology of Exercise, 2012)
The increase in cases of eating disorders, particularly among sportsmen and women, has taken on worrying proportions over recent years. Male and female athletes competing in sports that require the careful control of body weight and link slight builds with high performance (as is often the case in artistic events) are a high risk group for developing eating disorders. The aim of this study was to present the various types of eating disorder and their frequency in the world of sport. It also focused on the root causes of eating disorders, the effect they have on the body and, moreover, measures for their prevention and treatment. In this regard, the experiences of five former competitive rhythmic gymnasts, with years of experience in the sport and medals to their names, were carefully studied. An in-depth phenomenological study was conducted using open, semi-structured interviews in order to explore and understand the ways in which these individuals related to food and nutrition during their time as athletes. The results showed that the sportswomen taking part in the survey ran the risk of suffering from eating disorders for two main reasons. First, they displayed behaviours and personality traits common to people with eating disorders. And second, they submitted to the limitation or complete cessation of their food intake forced upon them by their environment (by coaches, parents, etc.).